I Was a Teen Rock Star! - Mohammed, A H (Nigeria, 2021)
This is all Lanre Bandele dreams about - even though he is a lonely and unhappy schoolboy, flunking his exams and abandoned by his parents. Yet how far will he go? Can wishes come true? Maybe... Lanre discovers an unexpectedly different world as he embarks on his journey...
Keywords: Adventure; Juvenile Fiction